In-plane ordered multi-component MAX phase materials and MXene materials and preparation methods and uses thereof
Through the etching technology of in-plane order multi-component MAX phase materials and MXene materials, the problem that the size of the metasurface microstructure is difficult to reach the nanoscale, atomic level regulation is achieved, and the materials are given new performances, and multiple fields are Application prospects.
Patent Information
- Application Number
- CN202111032348.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-03
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-09-03
AI Technical Summary
Existing metasurface processing technology is difficult to achieve nanoscale microstructure size, resulting in the inability to achieve extraordinary optical or electromagnetic properties.
By developing in-plane ordered multi-component MAX phase materials and MXene materials, selectively etch atoms in the material, obtain ordered vacancies or multi-vacancies MXene materials, realize atomic-level microstructure control, and prepare metasurfaces.
It realizes macro-physical characteristics such as electromagnetic, optical, and sound that traditional materials cannot have, and has a wide range of application prospects, such as anti-corrosion coatings, high-temperature coatings, nuclear radiation protection, catalysis, sensors, electronic devices, supercapacitors, electromagnetic shielding and absorption Wave material.
Smart Images

Figure CN115744906B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new materials, and in particular to a multi-component MAX phase material and a MXene material and a preparation method thereof. Background Art
[0002] Metamaterials refer to artificial composite structures or composite materials with extraordinary material properties that natural materials do not have. The design idea is to use some artificial structures with special functions as the basic crystal, and to extrapolate the ordered structure at the atomic level to the ordered arrangement at other levels. Metamaterials mainly present macroscopic physical characteristics such as electromagnetic, optical, and acoustic that traditional materials do not have by precisely designing the geometric shape, size, and arrangement of microstructure units. In particular, some breakthroughs have triggered disruptive changes in multiple fields such as communications, stealth, imaging detection, and information processing. For example, information metamaterials can quickly control electromagnetic waves, including amplitude control, polarization control, phase control, etc. In addition, information metamaterials can perform a variety of convolution operations, providing a new architecture for communication, which is expected to break through the bottleneck of AD / DA and realize a very simple high-speed communication system, and realize different high-speed modulation communications through space coding, time coding, and frequency domain coding; in the field of radar, it can provide a new architecture for radar imaging, which is expected to break through the bottleneck of high complexity of the existing radar imaging system and realize a very simple high-resolution radar imaging system.
[0003] Metasurfaces are a type of two-dimensional metamaterial that can control incident light on a very thin layer of subwavelength structure. Compared with three-dimensional bulk metamaterials, metasurfaces can currently be prepared through electron beam exposure, focused ion beam etching, laser direct writing, self-assembly, nanoimprinting and other technologies; at the same time, due to their ultra-light and ultra-thin characteristics, they are easy to integrate into miniaturized devices to reduce the weight and volume of the equipment. Due to their excellent phase, amplitude and polarization control capabilities, metasurfaces can be used to achieve wavefront manipulation (beam deflection, focusing, holography) and polarization conversion applications, and through the staggered arrangement of phases or polarization multiplexing methods, a multifunctional metasurface integrating multiple functions can be realized.
[0004] The microstructure size of metasurfaces manufactured by current processing technology is at the micron level, while the miniaturization and high frequency of devices are the main development directions of metasurfaces. In particular, optical frequency metasurfaces require the microstructure size to be reduced to below the nanoscale, which is difficult to achieve with existing processing technology. This results in the inability to achieve many extraordinary optical or electromagnetic properties. Summary of the invention
[0005] The purpose of the present invention is to provide a new type of in-plane ordered multi-component MAX phase material, use it as a raw material to obtain an in-plane ordered MXene material, and obtain an ordered vacancy or multi-vacancy MXene material by selectively etching the atoms in the in-plane ordered MXene material, thereby providing a new technical path for realizing atomic-level microstructure regulation and preparation of supersurfaces.
[0006] On the one hand, the present invention provides a multi-component MAX phase material with an in-plane order, whose chemical formula is expressed as (M x 'M" y ) n+ 1AX n ; wherein n is between 1 and 6, x+y=1; M' and M" are arranged in order in at least one crystal plane; the sum of the element types of M' and M" is more than three; M' is selected from one or more elements of Groups IVB, VB, VIB, VIIB, VIII, IB, and IIB, and M" is selected from at least one or more elements of Group IIIB, zirconium, lanthanide, and actinide.
[0007] In some embodiments, the above-mentioned M' is selected from one or more elements of Groups IVB, VB, VIB and VIIB; preferably, M' is selected from one or more elements of titanium, vanadium, chromium, manganese, niobium, molybdenum, technetium, hafnium, tantalum, tungsten or rhenium; and / or, the above-mentioned M" is selected from one or more elements of scandium, yttrium, zirconium, cerium, praseodymium, neodymium, samarium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, lutetium or ytterbium; and / or, the above-mentioned A is selected from at least one of aluminum, silicon, phosphorus, sulfur, gallium, germanium, arsenic, cadmium, indium, tin, thallium or lead; and / or, the above-mentioned X is at least one of carbon, nitrogen or boron.
[0008] In some embodiments, on the crystal plane perpendicular to the
[010] crystal axis and the (001) crystal plane, the atoms of M' and M" are arranged in an orderly manner according to a 2:1 period; and / or, in the multi-component MAX phase material, the atoms of each element of M' are randomly distributed at the M' position, and the atoms of each element of M" are randomly distributed at the M" position.
[0009] Another aspect of the present invention also includes a method for preparing the above-mentioned multi-component MAX phase material, comprising the following steps: 1) mixing solid powders containing M' phase, M" phase, A phase and X phase according to the stoichiometric ratio of the chemical formula, and ball milling to obtain a mixture; 2) heat treating the mixture obtained in step 1) in an inert gas protective atmosphere to obtain a multi-component MAX phase material; preferably, the heat treatment temperature is between 800°C and 3200°C.
[0010] Another aspect of the present invention also includes a multi-component MXene material obtained by etching the above-mentioned multi-component MAX phase material.
[0011] Another aspect of the present invention also includes a method for preparing a multi-component MXene material, comprising: etching A in the multi-component MAX phase material to obtain the multi-component MXene material, whose chemical formula is represented by (M' x M” y ) n+1 X n ; or, A and all or part of M' in the above multi-component MAX phase material are added to obtain the multi-component MXene material, whose chemical formula is represented by (M' x M” β ) n+1 X n , wherein 0≤β<y; or, A, all or part of M' and all or part of M' in the above multi-component MAX phase material are obtained to obtain the multi-component MXene material, whose chemical formula is expressed as (M' α M” β ) n+1 X n , where 0≤α<x, 0≤β<y.
[0012] In some embodiments, the etchant used for the above etching is selected from: one or more of halogen element gas, hydrogen halide gas, metal halide salt or ammonium salt of halogen element; or, the etchant is: hydrofluoric acid or acid solution + fluoride salt system.
[0013] The present invention also provides a use of the multi-component MAX phase material in the field of anti-corrosion coatings, high-temperature coatings, nuclear radiation protection or brushes.
[0014] The present invention also provides a use of the above-mentioned multi-component MXene material in anti-corrosion coatings, high-temperature coatings, nuclear radiation protection, catalysis, sensors, electronic devices, supercapacitors, batteries, electromagnetic shielding, absorbing materials or superconducting materials.
[0015] The present invention also provides a coating material comprising the above-mentioned multi-component MAX phase material and / or the above-mentioned multi-component MXene material.
[0016] The present invention also provides an electronic device comprising the above-mentioned multi-component MAX phase material and / or the above-mentioned multi-component MXene material.
[0017] The present invention also provides an energy storage device, characterized in that it contains the above-mentioned multi-component MAX phase material and / or the above-mentioned multi-component MXene material.
[0018] The beneficial effects of the present invention are:
[0019] The present invention provides a novel in-plane ordered multi-component MAX phase material and MXene material and a preparation method thereof. By etching the A component in the in-plane ordered multi-component MAX phase material, an in-plane ordered multi-component MXene material (two-dimensional material) is obtained, wherein the M component contains at least three elements. Since it has an ordered structure and multi-component atomic composition, it belongs to a novel super surface. The atoms in the in-plane ordered multi-component MXene material are further selectively etched to obtain a MXene material with ordered vacancies or a multi-vacancy MXene material, which also belongs to a novel super surface material. Due to the presence of abundant vacancies and atoms of multiple components, more single atom exposure can be formed, which can give this type of material new properties, presenting macroscopic physical characteristics such as electromagnetic, optical, and acoustic that traditional materials do not have, and has application prospects in anti-corrosion coatings, high-temperature coatings, nuclear radiation protection, catalysis, sensors, electronic devices, supercapacitors, batteries, electromagnetic shielding, absorbing materials or superconducting materials, and may trigger disruptive changes in multiple fields such as communications, stealth, imaging detection and information processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 and Figure 2 They are respectively the multi-component MAX phase material (M x 'M" y )2AX n and MXene materials (M x 'M" y )2X n Schematic diagram of the structure;
[0021] Figures 3 to 5 They are respectively the multi-component MAX phase material Mo in Example 2 of the present invention. 1.33 (Sc n Y 1-n ) 0.67 AlC, multi-component MXene material Mo 1.33 (Sc n Y 1-n ) 0.67 C and ordered vacancy MXene materials Mo 1.33 Schematic diagram of the structure of C;
[0022] Figures 6 to 8 They are respectively the multi-component MAX phase material (Mo) in Example 3 of the present invention. m W 1-m ) 1.33 (Sc n Y 1-n ) 0.67 AlC, multi-component MXene materials (Mo m W 1-m )1.33 (Sc n Y 1-n ) 0.67 C and ordered vacancy MXene materials (Mo m W 1-m ) 1.33 Schematic diagram of the structure of C;
[0023] Figures 9 to 11 They are respectively the multi-component MAX phase material (Mo) in Example 4 of the present invention. m W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) 0.67 AlC, multi-component MXene materials (Mo m W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) 0.67 C and ordered vacancy MXene materials (Mo m W p Cr 1-m-p ) 1.33 Schematic diagram of the structure of C;
[0024] Fig.12 The multi-component MAX phase material (Mo) in Example 5 of the present invention 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 ) SEM image of 2AlC;
[0025] Fig.13 The multi-component MAX phase material (Mo) in Example 5 of the present invention 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2AlC and ordered MAX phase materials (Mo 0.67 Y 0.34 ) XRD pattern of 2AlC;
[0026] Fig.14 and Fig.15 For Example 5 of the present invention (Mo 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 ) STEM image of 2AlC and EDS results of the corresponding position;
[0027] Fig.16 This is a high-resolution TEM image of a multi-component MAX phase material in Example 5 of the present invention, which is perpendicular to the
[010] crystal axis.
[0028] Fig.17 and Fig.18 The MXene material (Mo) obtained by etching in Example 6 of the present invention 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 ) SEM image of 2C;
[0029] Figures 19 to 21 They are respectively the multi-component ordered vacancy MXene materials (Mo) obtained by etching in Example 7 of the present invention. 0.221 W 0.221 Cr 0.221 )2CT x SEM, TEM and high-resolution TEM images;
[0030] Fig. 22 The multi-component MAX phase material (Mo) in Example 8 of the present invention 0.221 W 0.221 V 0.221 Y 0.17 Sc 0.17 ) Schematic diagram of the structure of 2AlC;
[0031] Fig.23 The multi-component MAX phase material (Mo) in Example 9 of the present invention 0.16 W 0.16 Cr 0.16 V 0.16 Y 0.17 Sc 0.17 ) Schematic diagram of the structure of 2AlC;
[0032] Fig.24 The multi-component MAX phase material (Mo) in Example 12 of the present invention 0.16 W 0.16 Cr 0.16 V 0.16 Y 0.34 ) Schematic diagram of the structure of 2AlC;
[0033] Fig.25 The multi-component MAX phase material (Mo) in Example 13 of the present invention 0.16 W 0.16 Cr 0.16 V 0.16 Sc 0.34 )Schematic diagram of the structure of 2AlC. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is described below by specific embodiments in conjunction with the accompanying drawings. It should be understood that the one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and does not limit the order of arrangement of each method or limit the scope of implementation of the present invention. Changes or adjustments in their relative relationships can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.
[0035] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0036] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.
[0037] Example 1
[0038] The present invention provides a multi-component MAX phase material with an in-plane order, the chemical formula of which is represented by (M x 'M" y ) n+1 AX n , wherein n is between 1 and 6, x+y=1; M' and M" are arranged in order in at least one crystal plane; wherein M' is selected from at least one element of Groups IVB, VB, VIB, VIIB, VIII, IB and IIB, and M" is selected from at least two elements of Group IIIB, zirconium, lanthanide or actinide.
[0039] The present invention also provides another in-plane ordered multi-component MAX phase material, whose chemical formula is also represented by (M x 'M" y ) n+ 1AX n , wherein n is between 1 and 6, x+y=1, M' and M" are arranged in order in at least one crystal plane; M' is selected from at least two elements of Groups IVB, VB, VIB, VIIB, VIII, IB and IIB, and M" is selected from at least one element of Group IIIB, zirconium, lanthanide or actinide.
[0040] Figure 1 A schematic diagram of the structure of a multi-component MAX phase material of the present invention is given (for the convenience of illustration, a schematic diagram of n=1 is given), Figure 1a and 1b are schematic diagrams of the crystal plane perpendicular to the
[010] crystal axis when viewed from the side and the (001) crystal plane when viewed from the top, respectively. Figure 1 It can be seen from a and 1b that the M' and M" atoms are arranged in an orderly manner. In particular, Figure 1 From the schematic diagram of a, which is a side view of a crystal plane perpendicular to the
[010] crystal axis, it can be seen that the atoms of M' and M" are arranged in an orderly manner according to a period of 2:1, but the present invention is not limited to this period ratio.
[0041] In some embodiments, M' is selected from one or more elements of Groups IVB, VB, VIB and VIIB, preferably, at least one selected from titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), niobium (Nb), molybdenum (Mo), technetium (Tc), hafnium (Hf), tantalum (Ta), tungsten (W) or rhenium (Re); these elements can be synthesized by sintering at a relatively low temperature of 1200°C to 2000°C.
[0042] In some embodiments, M" is selected from at least one of scandium (Sc), yttrium (Y), zirconium (Zr), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), lutetium (Lu) or ytterbium (Yb).
[0043] In some embodiments, A is selected from at least one of elements of Groups VIIB, VIII, IB, IIB, IIIA, IVA, VA or VIA, preferably, A is selected from at least one of aluminum (Al), silicon (Si), phosphorus (P), sulfur (S), gallium (Ga), germanium (Ge), arsenic (As), cadmium (Cd), indium (In), tin (Sn), thallium (Tl) or lead (Pb); X is at least one of carbon (C), nitrogen (N) or boron (B).
[0044] In some embodiments, M' includes one to four elements, and M" includes two elements; x=2 / 3, y=1 / 3, n=1, 2 or 3, and the atoms of M' and M" are arranged in an orderly manner according to a 2:1 period on the crystal plane perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0045] In some embodiments, M' includes two to four elements, and M" includes one element; x=2 / 3, y=1 / 3, n=1, 2 or 3, and the atoms of M' and M" are arranged in an orderly manner in a 2:1 period on the crystal plane perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0046] This embodiment also provides an in-plane ordered multi-component MXene material, which is obtained by etching away the A component in the MAX phase material of this embodiment, and its chemical formula is expressed as (M x 'M"y ) n+1 X n , its structural diagram is as follows Figure 2 shown.
[0047] Example 2
[0048] This embodiment provides a multi-component MAX phase material, whose chemical formula is Mo 1.33 (Sc n Y 1-n ) 0.67 AlC, where 0<n<1, Figure 3 The schematic diagram of its structure is given, and it can be seen that the two elements Sc and Y are distributed at the M” position.
[0049] This embodiment also provides a multi-component MXene material with an in-plane order. 1.33 (Sc n Y 1-n ) 0.67 The Al in AlC is etched away, and its chemical formula is Mo 1.33 (Sc n Y 1-n ) 0.67 C, its structural diagram is as follows Figure 4 As shown, from Figure 4 Figures 4a and 4b more clearly show that the Sc and Y elements are randomly distributed on the M" position and orderly distributed on the crystal planes perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0050] This embodiment also provides an ordered multi-vacancy transition metal carbide, which is obtained by further etching away the Sc and Y elements of the MXene material of this embodiment, and its chemical formula is Mo 1.33 C, whose structural schematic diagram is shown in Figure 5, it can be seen that the obtained Mo 1.33 C has orderly arranged vacancies; when the Sc and Y elements are incompletely etched, a multi-component MXene material with vacancies is obtained, and its chemical formula is Mo 1.33 (Sc n Y 1-n ) β C, where 0<β<0.67.
[0051] Further, in this embodiment, Mo 1.33 (Sc n Y 1-n ) 0.67 Etching the Y atoms in C can produce Mo 1.33 Sc 0.67n C.
[0052] Further, continue to select the etchant to the Mo obtained in this embodiment. 1.33 C is etched, part of Mo is etched away, and Mo is obtained. α C, where 0<α<1.33.
[0053] Example 3
[0054] This embodiment provides a multi-component MAX phase material, whose chemical formula is expressed as (Mo m W 1-m ) 1.33 (Sc n Y 1-n ) 0.67 AlC, where 0<m<1, 0<n<1, Figure 6 The schematic diagram of its structure is given, and it can be seen that the two elements Mo and W are distributed at the M' position, and the two elements Sc and Y are distributed at the M" position.
[0055] This embodiment also provides a multi-component MXene material with an in-plane order. m W 1-m ) 1.33 (Sc n Y 1-n ) 0.67 The Al in AlC is etched away, and its chemical formula is (Mo m W 1-m ) 1.33 (Sc n Y 1-n ) 0.67 C, its structural diagram is as follows Figure 7 As shown, from Figure 7 7a and 7b more clearly show that the two elements Mo and W are randomly distributed on the M' position, and the two elements Sc and Y are randomly distributed on the M" position, and are orderly distributed on the crystal plane perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0056] This embodiment also provides an ordered multi-vacancy transition metal carbide, which is obtained by further etching away the Sc and Y elements from the MXene material of this embodiment, and its chemical formula is expressed as (Mo m W 1-m ) 1.33 C, whose structural schematic diagram is shown in Figure 8, it can be seen that the obtained (Mo m W 1-m ) 1.33 C has orderly arranged vacancies; when the Sc and Y elements are incompletely etched, a multi-component MXene material with vacancies is obtained, and its chemical formula is expressed as (Mo m W 1-m ) 1.33 (Scn Y 1-n ) β C, where 0<β<0.67.
[0057] Further, in this embodiment, (Mo m W 1-m ) 1.33 (Sc n Y 1-n ) 0.67 The Y or Sc atoms in C are etched to form vacancies at the positions of Y or Sc, and (Mo m W 1-m ) 1.33 (Sc n ) 0.67 C or (Mo m W 1-m ) 1.33 (Y 1-n ) 0.67 C.
[0058] Further, continue to select the etching agent to obtain the (Mo m W 1-m ) 1.33 C is etched, and part of Mo and / or W is etched away to form new vacancies, and (Mo m W 1-m ) α C, where 0<α<1.33.
[0059] Example 4
[0060] This embodiment provides a multi-component MAX phase material, whose chemical formula is expressed as (Mo m W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) 0.67 AlC, where 0<m<1, 0<n<1, 0<p<1, Fig. 9 The schematic diagram of its structure is given, and it can be seen that the three elements Mo, W and Cr are distributed at the M' position, and the two elements Sc and Y are distributed at the M" position.
[0061] This embodiment also provides a multi-component MXene material with an in-plane order. m W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) 0.67 The Al in AlC is etched away, and its chemical formula is (Mom W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) 0.67 C, its structural diagram is as follows Fig.10 As shown, from Fig.10 a and 10b more clearly show that the three elements Mo, W and Cr are randomly distributed at the M' position, the two elements Sc and Y are distributed at the M" position, and are orderly distributed on the crystal planes perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0062] This embodiment also provides an ordered multi-vacancy transition metal carbide, which is obtained by further etching away the Sc and Y elements from the MXene material of this embodiment, and its chemical formula is expressed as (Mo m W p Cr 1-m-p ) 1.33 C, whose structural schematic diagram is shown in 11, it can be seen that the obtained (Mo m W p Cr 1-m-p ) 1.33 C has orderly arranged vacancies, and Mo, W and Cr are randomly arranged at the M' position; when Sc and Y elements are incompletely etched, a multi-component MXene material with vacancies is obtained, and its chemical formula is expressed as (Mo m W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) β C, where 0<β<0.67.
[0063] Further, in this embodiment, (Mo m W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) 0.67 The Y or Sc atoms in C are etched to form vacancies at the positions of Y or Sc, and (Mo m W p Cr 1-m-p ) 1.33 Sc 0.67n C or (Mo m W p Cr 1-m-p ) 1.33 (Y 1-n ) 0.67 C.
[0064] Further, continue to select the etching agent to obtain the (Mo m W p Cr 1-m-p ) 1.33 C is etched, and part of Mo, W and / or Cr is etched away to form new vacancies, and (Mo m W p Cr 1-m-p ) α C, where 0<α<1.33.
[0065] It can be seen from the above embodiments that the M component in the multi-component MAX phase material of the present invention contains at least three different elements. By etching the A component in the multi-component MAX phase material with order in the plane, an in-plane ordered multi-component MXene material (two-dimensional material) is obtained. Due to its ordered structure and multi-component atomic composition, it belongs to a new type of super surface; the atoms in the in-plane ordered multi-component MXene material are further selectively etched to obtain a MXene material with ordered vacancies or a MXene material with multiple vacancies, which also belongs to a new type of super surface material. Due to the presence of abundant vacancies and atoms of multiple components, more single atom exposure can be formed, which can give this type of material new properties, presenting macroscopic physical characteristics such as electromagnetic, optical, and acoustic that traditional materials do not have, and has application prospects in anti-corrosion coatings, high-temperature coatings, nuclear radiation protection, catalysis, sensors, electronic devices, supercapacitors, batteries, electromagnetic shielding, absorbing materials or superconducting materials, and may trigger disruptive changes in multiple fields such as communications, stealth, imaging detection and information processing.
[0066] The implementation of the technical route of the present invention includes screening the etchant. Optionally, the etchant includes: one or more of halogen element gas, hydrogen halide gas, metal halide salt or ammonium salt of halogen element; or, the etchant is: hydrofluoric acid or acid solution + fluoride salt system, but the present invention is not limited to this. Through a limited number of experiments, the best etchant and etching conditions for different atoms can be obtained, and atomic-level regulation can be achieved on MXene two-dimensional materials by changing the etchant and etching conditions.
[0067] The M' and M" positions in the above-mentioned embodiments can also be replaced by other types of atoms to obtain a variety of multi-component MAX phase materials, providing a substrate for further atomic selective etching, and then obtaining more types of new metasurface materials. Therefore, the purpose of the present invention is to provide a new idea and method for a new metasurface material, which can achieve atomic-level regulation and provide more basic material support for the development of new functional devices. The following is an illustration through specific experimental examples.
[0068] Example 5
[0069] This embodiment provides a multi-component in-plane ordered MAX phase material to prepare the (Mo) shown in Example 4. m W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) 0.67 AlC is taken as an example to illustrate, and the preparation method is as follows:
[0070] The transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Mo, W, Cr, Y and Sc, and the ratio is Mo:W:Cr:Y:Sc=0.443:0.443:0.443:0.34:0.34. The powders are mixed and evenly mixed and then placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 hours. Then, the ball-milled mixture powder is placed in a mold at 5 MPa cold pressing and then placed in a tubular furnace. Under argon as a protective gas, it is heated to 1500°C, kept warm for 10 hours, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase (Mo 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2AlC, and the results were as follows: Fig.12 As shown, (Mo 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2AlC has a three-dimensional block structure. 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2AlC and ordered MAX(Mo 0.67 Y 0.34 )2AlC was subjected to XRD comparative analysis, and the results are as follows Fig.13 As shown, (Mo 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 The (002) peak of )2AlC is located at 13.15°, while (Mo 0.67 Y 0.34 The position of the (002) peak of )2AlC is 12.90°. The results show that the simultaneous introduction of W, Cr, and Sc elements reduces the (002) crystal plane spacing. This can also be confirmed by the change in the average atomic radius. 0.443W 0.443 Cr 0.443 Y 0.34 Sc 0.34 and Mo 1.33 Y 0.67 The average atomic radius of the two atoms is 291.6 and 298.8 respectively. The decrease of the average atomic radius will reduce the (002) crystal plane spacing. The results of scanning transmission electron microscopy (STEM) and X-ray energy dispersive spectroscopy (EDS) analysis at the corresponding position are shown in the figure. Fig.14 and 15 As shown in Figure 1, Mo, W, Cr, Y, Sc, Al and C elements are evenly distributed, and the atomic percentage results show that the content of Mo, W, Cr, Y and Sc is close to the feed ratio. The spherical aberration electron microscope high-resolution TEM results perpendicular to the
[010] crystal axis are shown in Figure 1. Fig.16 As shown, the M1 and M2 sites are distributed in an orderly manner, and the ratio of M1 and M2 atoms is 2:1.
[0071] Example 6
[0072] This embodiment provides a multi-component in-plane ordered MXene material (Mo m W p Cr 1-m-p ) 1.33 (Sc n Y 1-n ) 0.67 C, obtained by etching the MAX phase material prepared in Example 5 as a raw material, and the preparation method is as follows:
[0073] Take 1g of the MAX phase (Mo 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2AlC is placed in a tubular furnace, a mixed gas of etching gas and inert gas is introduced into it, heated to a predetermined temperature and kept warm for a period of time, and then cooled to room temperature and taken out to obtain a powder product.
[0074] In some embodiments, the etching gas is selected to include a halogen gas or a hydrogen halide gas, including: Br2, Cl2, I2 or HF, HCl, HBr, HI.
[0075] In some embodiments, the etchant is a metal halide salt, including one or more of FeCl3, CoCl2, NiCl3, CuCl2, ZnCl2, CdCl2, FeBr3, CoBr2, NiBr3, CuBr2, ZnBr2, CdBr2, FeI3, CoI2, NiI3, CuI2, ZnI2 or CdI2, or an ammonium salt of a halogen element, including one or more of NH4F, NH4HF2, NH4Cl, NH4Br or NH4I. The solid etchant is placed in a tube furnace and decomposed into halogen element gas or hydrogen halide gas by heating, thereby achieving etching at the same time.
[0076] Preferably, the tube furnace is heated to a predetermined temperature of 400°C to 1200°C, the holding time is 5min to 12h, and the inert gas is argon. Since the multi-component MAX phase material in the present invention has a variety of different atoms, the etching conditions corresponding to different atoms are different. After a limited number of experiments, different types of etchants, etching times, heating temperatures and holding times can be selected to achieve etching of different atoms and control the material composition and position at the atomic level.
[0077] In a specific embodiment, 5 g of solid iodine was placed in a tube furnace, argon gas was introduced into the tube furnace, and the temperature was raised to 800 degrees Celsius and kept warm for 1 hour. After cooling to room temperature, a powder was obtained, and the obtained powder was characterized, as shown in FIG. Fig.17 As shown, it can be seen that it has an obvious accordion-like morphology, which is related to the etching of the Al element. 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2C.
[0078] In another specific embodiment, gaseous HCl gas is selected as an etchant, and a mixed gas of HCl and argon (the volume fraction of HCl is 10%) is introduced into a tube furnace, the temperature is raised to 600 degrees Celsius, and the temperature is kept for 1 hour. After cooling to room temperature, a powder is obtained, and the obtained powder is characterized, such as Fig.18 As shown, it can be seen that it has an obvious accordion-like morphology, which is related to the etching of the Al element. 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2C.
[0079] Example 7
[0080] This embodiment provides an ordered vacancy multi-component MXene material (Mo 0.221 W0.221 Cr 0.221 )2CT x , the preparation method is as follows:
[0081] Take 25 ml of 10% hydrofluoric acid as an etchant, take 1 g of the high entropy MAX phase (Mo 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2AlC was placed in an etchant, and a new etchant was replaced every 24 hours at room temperature under the same conditions. The reaction was continued for 72 hours. After the reaction, the accordion-shaped ordered vacancy medium entropy MXene two-dimensional material (Mo) was obtained by centrifugation, water washing and drying. 0.221 W 0.221 Cr 0.221 )2CT x , and then take the entropy of 1g accordion-shaped ordered vacancies (Mo 0.221 W 0.221 Cr 0.221 )2CT x 20 ml DMF was added and ultrasonicated for 30 min, and then centrifuged, washed with water and dried to obtain the two-dimensional (Mo 0.221 W 0.221 Cr 0.221 )2CT x Nanosheets.
[0082] The obtained nanosheets were tested by scanning electron microscope (SEM), and the results are as follows: Fig.19 As shown in Figure 1, it can be seen that its morphology is accordion-shaped, indicating the occurrence of etching reaction. Transmission electron microscopy TEM, the results are as follows Fig. 20 As shown, the prepared (Mo 0.221 W 0.221 Cr 0.221 )2CT x It is a two-dimensional flexible sheet. Spherical aberration electron microscope high-resolution TEM, the results are as follows Fig.21 As shown, the prepared (Mo 0.221 W 0.221 Cr 0.221 )2CT x Structure with ordered double vacancies.
[0083] Example 8
[0084] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is expressed as (Mo m W p V 1-m-p ) 1.33 (Sc n Y 1-n )0.67 AlC, wherein 0<m<1, 0<n<1, 0<p<1, three elements of Mo, W and V are distributed at the M' position, and two elements of Sc and Y are distributed at the M" position. The preparation method is as follows:
[0085] The transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Mo, W, V, Y, and Sc, and the ratio is Mo:W:V:Y:Sc=0.443:0.443:0.443:0.34:0.34. The powders are mixed and evenly mixed and placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 hours. Then, the ball-milled mixture powder is placed in a mold at 5 MPa cold pressing and placed in a tubular furnace. Under argon as a protective gas, it is heated to 1500°C, kept warm for 10 hours, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase (Mo 0.221 W 0.221 V 0.221 Y 0.17 Sc 0.17 )2AlC. Its structural diagram is as follows Fig. 22 As shown, from Fig. 22 a and 22b more clearly show that the three elements Mo, W and V are randomly distributed at the M' position, the two elements Sc and Y are distributed at the M" position, and are orderly distributed on the crystal planes perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0086] Take 10% hydrofluoric acid as the etchant and take the resulting high entropy MAX phase (Mo 0.221 W 0.221 Cr 0.221 Y 0.17 Sc 0.17 )2AlC is placed in an etchant and the reaction is continued for 36 hours to obtain a multi-component MXene material in which Al and part of Y are etched.
[0087] Example 9
[0088] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is expressed as (Mo m W p Cr q V 1-m-p-q ) 1.33 (Sc n Y 1-n ) 0.67 AlC, wherein 0<m<1, 0<n<1, 0<p<1, 0<q<1, four elements Mo, W, Cr and V are distributed at the M' position, and two elements Sc and Y are distributed at the M" position. The preparation method is as follows:
[0089] Transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Mo, W, Cr, V, Y, and Sc, and the ratio is Mo:W:Cr:V:Y:Sc=0.333:0.333:0.333:0.333:0.34:0.34. The powders are mixed and evenly mixed and placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 hours. Then, the ball-milled mixture powder is placed in a mold at 5 MPa cold pressing and placed in a tubular furnace. Under argon as protective gas, it is heated to 1500°C, kept warm for 10 hours, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase (Mo 0.16 W 0.16 Cr 0.16 V 0.16 Y 0.17 Sc 0.17 )2AlC. Its structural diagram is as follows Fig.23 As shown, from Fig.23 a and 23b more clearly show that the four elements Mo, W, Cr and V are randomly distributed at the M' position, the two elements Sc and Y are distributed at the M" position, and are orderly distributed on the crystal planes perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0090] Example 10
[0091] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is expressed as (Mo m W p Tc q Ta 1-m-p-q ) 1.33 (Sc n Y 1-n ) 0.67 AlC, wherein 0<m<1, 0<n<1, 0<p<1, 0<q<1, four elements of Mo, W, Tc and Ta are distributed at the M' position, and two elements of Sc and Y are distributed at the M" position. The preparation method is as follows:
[0092] Transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Mo, W, Tc, Ta, Y, and Sc, and the ratio is Mo:W:Tc:Ta:Y:Sc=0.333:0.333:0.333:0.333:0.34:0.34. The powders are mixed and evenly mixed and placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 hours. Then, the ball-milled mixture powder is placed in a mold at 5 MPa cold pressing and placed in a tubular furnace. Under argon as protective gas, it is heated to 1200°C, kept warm for 10 hours, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase (Mo0.16 W 0.16 Tc 0.16 Ta 0.16 Y 0.17 Sc 0.17 )2AlC. After etching the Al element with an etchant, MXene material (Mo 0.16 W 0.16 Tc 0.16 Ta 0.16 Y 0.17 Sc 0.17 )2C; By further etching the metal atoms Y and Sc, MXene materials with ordered vacancies (Mo 0.16 W 0.16 Tc 0.16 Ta 0.16 )2C.
[0093] Embodiment 11
[0094] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is (Fe m Co p Ni q Cu 1-m-p-q ) 1.33 (Sc n Y 1-n ) 0.67 AlC, wherein 0<m<1, 0<n<1, 0<p<1, 0<q<1, four elements of Fe, Co, Ni and Cu are distributed at the M' position, and two elements of Sc and Y are distributed at the M" position. The preparation method is as follows:
[0095] Transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Fe, Co, Ni, Co, Y and Sc, and the ratio is Fe:Co:Ni:Cu:Y:Sc=0.333:0.333:0.333:0.333:0.34:0.34. The powders are mixed and evenly mixed and placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 h. Then, the ball-milled mixture powder is placed in a mold at 5 MPa cold pressing and placed in a tubular furnace. Under argon as protective gas, it is heated to 3200°C, kept warm for 10 h, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase (Fe 0.16 Co 0.16 Ni 0.16 Cu 0.16 Y 0.17 Sc 0.17 )2AlC. After etching the Al element with an etchant, MXene material (Fe 0.16 Co0.16 Ni 0.16 Cu 0.16 Y 0.17 Sc 0.17 )2C; By further etching the metal atoms Y and Sc, MXene materials with ordered vacancies (Fe 0.16 Co 0.16 Ni 0.16 Cu 0.16 )2C.
[0096] Example 12
[0097] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is expressed as (Mo m W n Cr p V 1-m-n-p ) 1.33 Y 0.67 AlC, wherein 0<m<1, 0<n<1, 0<p<1, four elements Mo, W, Cr and V are distributed at the M' position, and the Y element is distributed at the M" position. The preparation method is as follows:
[0098] The transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Mo, W, Cr, V, and Y, and the ratio is Mo:W:Cr:V:Y=0.333:0.333:0.333:0.333:0.67. The powders are mixed and evenly mixed and placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 hours. Then, the ball-milled mixture powder is placed in a mold at 5 MPa cold pressing and placed in a tubular furnace. Under argon as a protective gas, it is heated to 1500°C, kept warm for 10 hours, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase (Mo 0.16 W 0.16 Cr 0.16 V 0.16 Y 0.34 )2AlC. Its structural diagram is as follows Fig.24 As shown, from Fig.24 a and 24b more clearly show that the four elements Mo, W, Cr and V are randomly distributed at the M' position, the Y element is distributed at the M" position, and is orderly distributed on the crystal planes perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0099] Example 13
[0100] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is expressed as (Mo m W n Cr p V 1-m-n-p) 1.33 Sc 0.67 AlC, wherein 0<m<1, 0<n<1, 0<p<1, four elements of Mo, W, Cr and V are distributed at the M' position, and the Sc element is distributed at the M" position. The preparation method is as follows:
[0101] Transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Mo, W, Cr, V, and Sc, and the ratio is Mo:W:Cr:V:Sc=0.333:0.333:0.333:0.333:0.67. The powders are mixed and evenly mixed and placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 hours. Then, the ball-milled mixture powder is placed in a mold at 5 MPa cold pressing and placed in a tubular furnace. Under argon as protective gas, it is heated to 1500°C, kept warm for 10 hours, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase (Mo 0.16 W 0.16 Cr 0.16 V 0.16 Sc 0.34 )2AlC. Its structural diagram is as follows Fig.25 As shown, from Fig.25 a and 25b more clearly show that the four elements Mo, W, Cr and V are randomly distributed at the M' position, the Sc element is distributed at the M" position, and is orderly distributed on the crystal planes perpendicular to the
[010] crystal axis and the (001) crystal plane.
[0102] Embodiment 14
[0103] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is (Ti m Mn n V 1-m-n ) 1.33 Sc 0.67 AlC, wherein 0<m<1, 0<n<1, Ti, Mn and V are distributed at the M' position, and Sc is distributed at the M" position. The preparation method is as follows:
[0104] The transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Ti, Mn and V in a ratio of Ti:Mn:V:Sc=0.444:0.444:0.444:0.67. The powders are mixed uniformly and placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 hours. The ball-milled mixture powder is then placed in a mold at 5 MPa cold pressure and placed in a tubular furnace. Under argon as a protective gas, the mixture is heated to 1500°C, kept warm for 10 hours, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase Ti0.44 Mn 0.44 V 0.44 Sc 0.67 AlC. After etching the Al element with an etchant, the MXene material Ti can be obtained. 0.44 Mn 0.44 V 0.44 Sc 0.67 C.
[0105] Embodiment 15
[0106] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is (Nb m Hf 1-m ) 1.33 Zr 0.67 AlC, wherein 0<m<1, Nb, and Hf are distributed at the M' position, and Zr is distributed at the M" position. The preparation method is as follows:
[0107] The transition metal powder, aluminum powder and flake graphite are mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder is composed of Nb and Hf in a ratio of Nb:Hf:Zr=0.67:0.67:0.67. The powders are mixed uniformly and placed in an agate ball mill for ball milling. The ball milling speed is 600 rpm and the ball milling time is 20 hours. Then, the ball-milled mixture powder is placed in a mold at 5 MPa cold pressure and placed in a tubular furnace. Under argon as a protective gas, it is heated to 1800°C, kept warm for 10 hours, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase Nb 0.67 Hf 0.67n Zr 0.67 AlC. After etching the Al element with an etchant, the MXene material Nb 0.67 Hf 0.67 Zr 0.67 C.
[0108] Example 16
[0109] This embodiment provides another in-plane ordered multi-component MAX phase material, whose chemical formula is (Nb m Re 1-m ) 1.33 (Zr n Ce 1-n ) 0.67 AlC, wherein 0<m<1, 0<n<1, Nb and Re elements are distributed at the M' position, and Zr and Ce elements are distributed at the M" position. The preparation method is as follows:
[0110] The transition metal powder, aluminum powder and flake graphite were mixed uniformly in a stoichiometric ratio of 2:1.3:1, wherein the transition metal powder was composed of Nb and Hf in a ratio of Nb:Re:Zr:Ce=0.67:0.67:0.333:0.333. The powders were mixed uniformly and placed in an agate ball mill for ball milling at a ball milling speed of 600 rpm for 20 h. The ball milled mixture powder was then placed in a mold at 5 MPa cold pressure and placed in a tubular furnace. Under argon as a protective gas, the mixture was heated to 2000°C, kept warm for 10 h, and naturally cooled to room temperature to obtain a high entropy ordered MAX phase (Nb 0.34 Re 0.34 Zr 0.17 Ce 0.17 )2AlC. After etching the Al element with an etchant, MXene material (Nb 0.34 Re 0.34 Zr 0.17 Ce 0.17 )2C; By further selectively etching the metal atoms therein, MXene materials containing ordered vacancies can be obtained.
[0111] Embodiment 17
[0112] The present embodiment provides an electronic device, which is a hydrogen evolution catalytic device. The MXene material containing vacancies after etching of the present invention is configured into a dispersion liquid, which is dripped onto a glassy carbon electrode. After evaporating the solution, a hydrogen evolution catalytic device containing the MXene material of the present invention is obtained. Since more single atoms are exposed in the MXene containing vacancies, the catalytic performance of the material can be improved, and it has great application prospects in the field of catalysts.
[0113] In a specific embodiment, the (Mo) obtained in Example 7 0.221 W 0.221 Cr 0.221 )2CT x The dispersion was prepared into 2 mg / mL and drop-coated on an L-glassy carbon electrode to prepare a hydrogen evolution catalytic device.
[0114] Embodiment 18
[0115] This embodiment provides a protective coating, wherein the multi-component MAX phase material of the present invention is ground into fine powder, added into a liquid matrix, mixed evenly, and then the liquid matrix is coated into a film, and after curing and forming, a coating containing the MAX phase material is obtained, which can be used as a thermal barrier coating, an anti-corrosion coating, or an electromagnetic shielding coating, etc.
[0116] The multi-component MXene material of the present invention is added to a liquid matrix to obtain a protective coating containing the multi-component MXene material. The two-dimensional MXene material can form an ultra-thin protective film in the coating, and can also be used as a thermal barrier coating, an anti-corrosion coating or an electromagnetic shielding coating.
[0117] Embodiment 19
[0118] The present embodiment provides an energy storage device, which is a battery, wherein the negative electrode material contains metallic lithium and the multi-component MXene material of the present invention. By doping the multi-component MXene material of the present invention, the surface tension of the molten metallic lithium can be reduced, thereby obtaining an ultra-thin metallic lithium composite material and using it as the negative electrode material of the battery.
[0119] The multi-component MAX phase material or MXene material of the present invention can also be used in other types of energy storage devices, such as supercapacitors.
[0120] The multi-component MAX phase material or MXene material of the present invention can also be added as a modified material to other matrices to form a composite material, such as being compounded with a polymer material.
[0121] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. An in-plane ordered multi-component MAX phase material, characterized in that: The chemical formula of the multi-component MAX phase material is expressed as (M x 'M" y ) n+1 AX n ; Wherein, n is between 1 and 6, x+y=1; The sum of the element types of M' and M" is three or more; M' is selected from one or more elements of Groups IVB, VB, VIB, VIIB, VIII, IB, and IIB; On the crystal planes perpendicular to the [010] crystal axis and the (001) crystal plane, the atoms of M' and M" are arranged in an orderly manner according to a period of 2:1; The M" is selected from one or more elements of scandium, yttrium, zirconium, cerium, praseodymium, neodymium, samarium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, lutetium or ytterbium; The A is selected from at least one of aluminum, silicon, phosphorus, sulfur, gallium, germanium, arsenic, cadmium, indium, tin, thallium or lead; And / or, X is at least one of carbon, nitrogen or boron.
2. The multi-component MAX phase material according to claim 1, characterized in that: The M' is selected from one or more elements of Groups IVB, VB, VIB and VIIB.
3. The multi-component MAX phase material according to claim 2, characterized in that: The M' is selected from one or more elements of titanium, vanadium, chromium, manganese, niobium, molybdenum, technetium, hafnium, tantalum, tungsten or rhenium.
4. The multi-component MAX phase material according to any one of claims 1 to 3, characterized in that In the multi-component MAX phase material, atoms of each element of M' are randomly distributed at the M' position, and atoms of each element of M" are randomly distributed at the M" position.
5. A method for preparing a multi-component MAX phase material according to any one of claims 1 to 4, characterized in that the steps include: 1) mixing solid powders containing M' phase, M" phase, A phase and X phase according to the stoichiometric ratio of the chemical formula, and ball milling to obtain a mixture; 2) heat treating the mixture obtained in step 1) in an inert gas shielding atmosphere to obtain a multi-component MAX phase material.
6. The preparation method according to claim 5, characterized in that: The heat treatment temperature is between 800°C and 3200°C.
7. A multi-component MXene material obtained by etching the multi-component MAX phase material according to any one of claims 1 to 4.
8. A method for preparing a multi-component MXene material, characterized in that: The preparation method comprises: The A in the multi-component MAX phase material according to any one of claims 1 to 4 is etched to obtain the multi-component MXene material, whose chemical formula is represented by (M' x M” y ) n+1 X n ; Or, A and all or part of M' in the multi-component MAX phase material according to any one of claims 1 to 4 are added to obtain the multi-component MXene material, whose chemical formula is represented by (M' x M” β ) n+1 X n , where 0≤β<y; Or, A, all or part of M' and all or part of M' in the multi-component MAX phase material according to any one of claims 1 to 4 are combined to obtain the multi-component MXene material, whose chemical formula is represented by (M' α M” β ) n+1 X n , where 0≤α<x, 0≤β<y.
9. A preparation method according to claim 8, characterized in that: The etchant used for the etching is selected from: one or more of halogen element gas, hydrogen halide gas, metal halide salt or ammonium salt of halogen element; or, the etchant is: hydrofluoric acid or acid solution + fluoride salt system.
10. Use of the multi-component MAX phase material according to any one of claims 1 to 4 in the field of anti-corrosion coatings, high-temperature coatings, nuclear radiation protection or brushes.
11. A use of the multi-component MXene material as claimed in claim 7 in anti-corrosion coatings, high-temperature coatings, nuclear radiation protection, catalysis, sensors, electronic devices, supercapacitors, batteries, electromagnetic shielding, absorbing materials or superconducting materials.
12. A coating material, characterized in that: Containing the multi-component MAX phase material according to any one of claims 1 to 4 and / or the multi-component MXene material according to claim 7.
13. An electronic device, characterized in that: Containing the multi-component MAX phase material according to any one of claims 1 to 4 and / or the multi-component MXene material according to claim 7.
14. An energy storage device, characterized in that: Containing the multi-component MAX phase material according to any one of claims 1 to 4 and / or the multi-component MXene material according to claim 7.
